Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Salcedo Hermenegildo, Solange (2018)
In the present research work we will delve into the analysis of a possible income of the Fast Retailing company, with its leading brand Uniqlo, to the Peruvian market. Initially, the company is analyzed with emphasis on the 9 divisions made by Alexander Osterwalder in order to gain an in-depth knowledge of the business, the way it operates and the competitive advantages it has with the companies of the same line of business. For this study, the Peruvian market and its potential will be analyzed, to identify if it represents a potential market where it is convenient to bring foreign investment to generate high profitability or otherwise to discard it as a possible new market to start operating. For this, the opportunities and threats that this could generate are thoroughly analyzed and, likewise, each of the external factors such as political, economic, technological and social factors will be analyzed in order to have a clearer vision of the market to enter.